Thermodynamic nature of irreversibility in active matter - Lennart Dabelow; Ralf Eichhorn (Physical Review Research)
Active matter describes systems whose constituents convert energy from their surroundings into directed motion, such as bacteria or catalytic colloids. We establish a thermodynamic law for dilute suspensions of interacting active particles in the form of a remarkable direct link between their dynamics and thermodynamics: The rate at which irreversibility is built up in the nonequilibrium steady state is a state function of the thermodynamic system parameters, namely, the number of particles, the temperature, and, as a distinctive characteristic of active matter, the swim pressure. Like in the famous fluctuation theorems of stochastic thermodynamics, irreversibility is a dynamical measure that quantifies the amount by which microscopic particle trajectories break time-reversal symmetry, without reference to the typically unobservable processes underlying self-propulsion. We derive the result for the paradigmatic model of active Ornstein-Uhlenbeck particles with short-ranged repulsive interactions. Based on numerical simulations and heuristic arguments, we furthermore present a refined relation whose validity extends from the dilute into the phase-separated (MIPS) regime.